COOPERATION BETWEEN INTERPOL INDONESIA - COLOMBIA IN HANDLING TRANSNATIONAL CRIMES (CASE STUDY M. NAZARUDDIN) - Rahmad, Riko; Deni, Fitra (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2024)
Transnasional Crime as a from of crime that could potentially threaten the life of the community such as the economy, social orderl and security, both nationally and regionally. The development of transnational crime in Indonesia as the impact of globalization are also other factors relating to the movement of people from one country to another region or from one region to another. All these factors led to the emergence of transnational crime. Interpol is an internasional organization formed to handle transnational crimes. In handling transnasional crimes, Interpol has a global communication system (1-24/7) which is very effective in the exchange of information between Interpol member countries in dealing with transnasional crimes. Interpol also involves in effective cooperation in handling transnasional crimes through various notifications that are given by the Interpol, one through red notices. Develomment of a crime that was once a crime of corruption of national and derived from national law into internasional crime transnasional organized, because of corruption related to economic crime, as well as the joint can be fragile democracy in a country. Internasional cooperation is needed in order to combat crimes that are transnasional corruption.